Wanita dalam Chanoyu pada Novel “The Life of an Amarous Man” Karya Ihara Saikaku (Kajian Sastra dan Budaya Jepang ) - Alo Karyati (Universitas Negeri Semarang, 2022)
This study examines the role of women in chanoyu or the Japanese tea ceremony contained in the novel